2017
DOI: 10.18632/oncotarget.15301
|View full text |Cite
|
Sign up to set email alerts
|

SNORA74B gene silencing inhibits gallbladder cancer cells by inducing PHLPP and suppressing Akt/mTOR signaling

Abstract: Small nucleolar RNAs (snoRNAs) have been implicated in the development of many cancers. We therefore examined the differential expression of snoRNAs between gallbladder cancer (GBC) tissues and matched adjacent non-tumor tissues using expression microarray analysis with confirmation by quantitative real-time PCR (qRT-PCR). Western blot analysis showed that SNORA74B levels were higher in GBC than non-tumor tissues. SNORA74B expression was positively associated with local invasion, advanced TNM stage, CA19-9 lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…mTOR is activated by Akt and negatively regulates autophagy (28). Extensive research has indicated that inhibiting the Akt/mTOR pathway contributes to autophagy in cancer cells (29,30). In our study, TTF1-NP inhibited the Akt/mTOR pathway and decreased p-Akt (Ser473) and p-mTOR (Ser2448) levels in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 49%
“…mTOR is activated by Akt and negatively regulates autophagy (28). Extensive research has indicated that inhibiting the Akt/mTOR pathway contributes to autophagy in cancer cells (29,30). In our study, TTF1-NP inhibited the Akt/mTOR pathway and decreased p-Akt (Ser473) and p-mTOR (Ser2448) levels in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 49%
“…The next identified tumor subtype is UCEC. Tumor-associated snoRNAs, such as ACA56 [60], HBII-336 [61], SNORD19 [41], and U19 [56,62], have been screened out using four quantitative parameters for UCEC identification. Among these four parameters, U19 is a relatively unique parameter with expression level higher than 119, indicating its potential role in tumor subtyping.…”
Section: Discussionmentioning
confidence: 99%
“…Among these four parameters, U19 is a relatively unique parameter with expression level higher than 119, indicating its potential role in tumor subtyping. According to recent publications [56,62], snoRNA U19 (SNORA74), as an H/ACA box snoRNA, contributes to the regulation of the famous AKT/mTOR signaling pathway. The expression level of such gene has been screened out and functionally confirmed to participate in multiple tumor subtypes including UCEC and gallbladder cancer [62].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of two other snoRNAs, snoRA47 and ACA11, are also high in hepatocellular carcinoma tissues compared to normal tissues [49,50]. snoRA74 (U19), responsible for modifying the two most conserved Ψs on 28S rRNA, 3741 and 3743 is found to be up-regulated in gallbladder cancer [51]. These positions are conserved from bacteria (protein only modification) to humans [1,38,41].…”
Section: Box H/aca Guide Rnas In Human Diseasementioning
confidence: 99%